2021
DOI: 10.1002/rmv.2300
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressor of Cytokine Signalling family of proteins and their potential impact on COVID‐19 disease progression

Abstract: Summary The family of Suppressor of Cytokine Signalling (SOCS) proteins plays pivotal roles in cytokine and immune regulation. Despite their key roles, little attention has been given to the SOCS family as compared to other feedback regulators. To date, SOCS proteins have been found to be exploited by viruses such as herpes simplex virus (HSV), hepatitis B virus (HBV), hepatitis C virus (HCV), Zika virus, respiratory syncytial virus (RSV), Ebola virus, influenza A virus (IAV) and SARS‐CoV, just to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 101 publications
(220 reference statements)
0
8
0
Order By: Relevance
“…However, the ISGs are not the only antiviral factors. Although most ISGs encode proteins capable of inhibiting different stages of the SARS-CoV-2 replication cycle ( 143 , 261 , 262 ), a few ISGs, including SOCS, USP18, and IFI44, can promote viral infection of the host ( 263 268 ). It was shown that silencing of IFI44 inhibits viral replication and overexpression of IFI44 promotes viral production due to negative regulation of the IFN-I pathway by IFI44 ( 195 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ISGs are not the only antiviral factors. Although most ISGs encode proteins capable of inhibiting different stages of the SARS-CoV-2 replication cycle ( 143 , 261 , 262 ), a few ISGs, including SOCS, USP18, and IFI44, can promote viral infection of the host ( 263 268 ). It was shown that silencing of IFI44 inhibits viral replication and overexpression of IFI44 promotes viral production due to negative regulation of the IFN-I pathway by IFI44 ( 195 ).…”
Section: Discussionmentioning
confidence: 99%
“…Known as PAMPs, these foreign viral molecules trigger the host innate immune system [58,173]. PAMPs are recognized by PRRs which include TLRs and RLRs [15,174]. These interactions activate NF-κB to produce pro-inflammatory cytokines and IRFs that generate type I and III IFNs [175].…”
Section: Nsp15mentioning
confidence: 99%
“…N Packages viral genomic RNA into a helical ribonucleoprotein form. [14] In some patients, COVID-19 can lead to certain severe complications, such as septic shock, multiple organ failure, and the more pronounced acute respiratory distress syndrome [15]. In times of urgent need, drug repositioning represents a feasible approach to combat COVID-19.…”
mentioning
confidence: 99%
“…Afflicting more than 530 million individuals accompanied by 6.3 million deaths worldwide, SARS-CoV-2 infection continues to progress at a very rapid rate on a global scale [1]. The zoonotic origin of SARS-CoV-2 has been postulated to be bats, similar to its previous counterpart, SARS-CoV [2]. Despite exacting a lower estimated case fatality rate (3.4%) compared to its predecessors (9.6% for SARS-CoV, and 40% for MERS-CoV), SARS-CoV-2 shows greater transmissibility along with the rapid emergence of new variants [3].…”
Section: Introductionmentioning
confidence: 99%